Anion binding to a cationic europium(iii) probe enables the first real-time assay of heparan sulfotransferase activity. Issue 3 (24th December 2021) - Wheeler, Simon; Breen, Colum; Li, Yong; Hewitt, Sarah H.; Robertson, Erin; Yates, Edwin A.; Barsukov, Igor L.; Fernig, David G.; Butler, Stephen J.
Abstract : We present a new luminescent europium(iii )-based anion receptor that binds to PAP (adenosine-3′, 5′-diphosphate). The increased emission intensity and lifetime of the receptor-PAP complex was used to develop the first real-time assay of heparan sulfotransferase activity. Abstract : Sulfotransferases constitute a ubiquitous class of enzymes which are poorly understood due to the lack of a convenient tool for screening their activity. These enzymes use the anion PAPS (adenosine-3′-phosphate-5′-phosphosulfate) as a donor for a broad range of acceptor substrates, including carbohydrates, producing sulfated compounds and PAP (adenosine-3′, 5′-diphosphate) as a side product. We present a europium(iii )-based probe that binds reversibly to both PAPS and PAP, producing a larger luminescence enhancement with the latter anion. We exploit this greater emission enhancement with PAP to demonstrate the first direct real-time assay of a heparan sulfate sulfotransferase using a multi-well plate format. The selective response of our probe towards PAP over structurally similar nucleoside phosphate anions, and over other anions, is investigated and discussed. This work opens the possibility of investigating more fully the roles played by this enzyme class in health and disease, including operationally simple inhibitor screening.